2021
DOI: 10.3390/brainsci11070860
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Covid and Autism: Prevalence, Clinical Presentation and Vaccine Side Effects

Abstract: Background: Several neurobiological mechanisms have been proposed to support the hypothesis of a higher COVID-19 risk in individuals with autism spectrum disorder (ASD). However, no real-world data are available on this population. Methods: We compared the period prevalence (March–May 2020) and symptom presentation of COVID-19 infections between a sample of individuals with severe ASD (n = 36) and the staff personnel (n = 35) of two specialized centers. Anti-SARS-Cov-2 antibody positivity was used as a proxy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Only nine studies (16%) focussed, at least in part, on Autistic adults with intellectual disability [ 13 •, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For the 35 studies (64%) including Autistic adults’ self-report data, it is likely that participating adults did not have a co-occurring intellectual disability, since self-report requires the ability to understand and respond to questions (orally or in writing), usually without support.…”
Section: Resultsmentioning
confidence: 99%
“…Only nine studies (16%) focussed, at least in part, on Autistic adults with intellectual disability [ 13 •, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For the 35 studies (64%) including Autistic adults’ self-report data, it is likely that participating adults did not have a co-occurring intellectual disability, since self-report requires the ability to understand and respond to questions (orally or in writing), usually without support.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to many factors including parental oversight of autistic individuals and concern for more severe COVID-19 illness. A small study found no increased COVID-19 vaccine side-effects, such as fever or fatigue, in autistic patients compared to non-autistic patients ( 18 ). These data support favorable trends in combating the pandemic in autistic individuals, and providers should continue to refer to FDA recommendations regarding updates on vaccination age cut-offs and booster doses to best protect autistic patients.…”
Section: Medical Carementioning
confidence: 96%
“…Its main characteristics are differences in social communication and interaction and repetitive and restrictive behaviours, including differences in sensory preferences (5). Whilst several genetical and immunological characteristics of autism have been hypothesised to affect COVID-19 infection, severity, and mortality risk (68), few studies have focused on differences in the clinical profiles of autistic people and the general population. Both physical and mental health conditions, such as obesity (2,3), gastrointestinal symptoms (3) and mental health conditions (9,10) have been associated with increased COVID-19 infection, disease severity and mortality in the general population.…”
Section: Introductionmentioning
confidence: 99%